2010
DOI: 10.2298/bah1006361s
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of oxidative stress in broilers during summer

Abstract: A comparative study on antistressor and antioxidative effects of synthetic vitamin C and polyherbal feed premix Ayucee supplementation in broilers was conducted during the summer months of June-July when the mean temperature-humidity index was 84.74?2.51. Day old broiler chicks (n =60) were randomly divided into three groups. Control group I was given basal diet and treatment groups (II&III) were supplemented with Synthetic vitamin C (100g/tonne of feed) and Ayucee (100g/tonne of feed) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…In the present study, protective effect of ashwagandha could be due to its antioxidant defensive mechanism by scavenging free radicals and these results are in harmony with the earlier studies of Harikrishnan et al, (2008) and Sujatha et al, (2010). Selenium alleviated CPF induced liver damage in the present study, which could be due to its antioxidant properties as it is a constituent of selenoenzyme-GSH-Pxand these findings are in agreement with the previous studies of Kaushal et al, (2011) and Abdel-Rahman et al, (2017).…”
Section: Haematologysupporting
confidence: 93%
“…In the present study, protective effect of ashwagandha could be due to its antioxidant defensive mechanism by scavenging free radicals and these results are in harmony with the earlier studies of Harikrishnan et al, (2008) and Sujatha et al, (2010). Selenium alleviated CPF induced liver damage in the present study, which could be due to its antioxidant properties as it is a constituent of selenoenzyme-GSH-Pxand these findings are in agreement with the previous studies of Kaushal et al, (2011) and Abdel-Rahman et al, (2017).…”
Section: Haematologysupporting
confidence: 93%
“…A phytobiotic such as licorice is used as blood purifier and immunity enhancer because it boosts white blood cells and ultimately increases interferon levels. The results of the current investigation support the fact that supplementation of feed with Ashwagandha root powder may protect RBC from oxidative stress due to its antioxidant activity [22].…”
Section: Discussionsupporting
confidence: 79%
“…In another studies, [20] and [26] reported the increase in body weight when birds were supplemented with polyherbal feed premix containing E. officinalis.…”
Section: A Effect Of Pgc On Egg Production and Feed Intake Parametersmentioning
confidence: 99%